Dampak Kerugian Negara Akibat Korupsi : Analisis Studi Kasus di Negara Indonesia (Jurnal Kendali Akuntansi, 2025)
The purpose of this study is to analyze the state impact caused by each corruption case in Indonesia from 2022-2025. This research uses descriptive qualitative research. The data in this study are secondary data sourced from scientific journal articles, reports from anti-corruption organizations, such as TI, ICW, KPK, and mass media. Data collection techniques are in the form of literature studies with analysis techniques by analyzing data reduction or selecting relevant information, presenting data arranged systematically, and drawing conclusions. The results of this study show that these cases resulted in very significant state economic losses, reaching trillions of rupiah. In addition to financial losses, corruption also has a negative impact on the environment, infrastructure, business climate, and public trust in the government and BUMN. Extensive environmental damage occurred due to illegal mining practices, while BTS 4G projects were hampered in their construction, and in other cases reduced investor and public confidence. Overall, the corruption exposed weaknesses in oversight and governance systems in SOEs and government projects.